Management of Upper-Limb Spasticity Using Modern Rehabilitation Techniques versus Botulinum Toxin Injections Following Stroke - Ana Maria Bumbea; Otilia Constantina Rogoveanu; Adina Turcu-Stiolica; Ionica Pirici; George Cioroianu; Diana Iulia Stanca; Oana Criciotoiu; Viorel Biciusca; Rodica Magdalena Traistaru; Danut Visarion Caimac (Life, 2023)
Our purpose is to emphasize the role of botulinum toxin in spasticity therapy and functional recovery in patients following strokes. Our retrospective study compared two groups, namely ischemic and hemorrhagic stroke patients. The study group (BT group) comprised 80 patients who received focal botulinum toxin as therapy for an upper limb with spastic muscle three times every three months. The control group (ES group) comprised 80 patients who received only medical rehabilitation consisting of electrostimulation and radial shockwave therapy for the upper limb, which was applied three times every three months. Both groups received the same stretching program for spastic muscles as a home training program. We evaluated the evolution of the patients using muscle strength, Ashworth, Tardieu, Frenchay, and Barthel scales. The analysis indicated a statistically significant difference between the two groups for all scales, with better results for the BT group (p < 0.0001 for all scales). In our study, the age at disease onset was an important prediction factor for better recovery in both groups but not in all scales. Better recovery was obtained for younger patients (in the BT group, MRC scale: rho = −0.609, p-value < 0.0001; Tardieu scale: rho = −0.365, p-value = 0.001; in the ES group, MRC scale: rho = −0.445, p-value < 0.0001; Barthel scale: rho = −0.239, p-value = 0.033). Our results demonstrated the effectiveness of botulinum toxin therapy compared with the rehabilitation method, showing a reduction of the recovery time of the upper limb, as well as an improvement of functionality and a reduction of disability. Although all patients followed a specific kinetic program, important improvements were evident in the botulinum toxin group.